“Blame Miners, not the Government”: An Image Repair Perspective of the Oyo State Government’s Response to the Ibadan Explosion in Nigeria - Mobolaji, Adeola Obafemi (Journal of Communication and Public Relations, 2025)
One compelling example of events that attracted public interest in crisis response and image repair is the episode of a deadly explosion that rocked Ibadan, the capital city of Oyo State, Nigeria, especially because of its implications for public safety, citizens’ well-being, and the government’s reputation. However, despite the prevalence of crises among Nigerian institutions, and how crises can be politicized to lead to more crises, there is a dearth of empirical investigations on the application of Benoit’s Image Repair, particularly regarding how the government repaired its reputation during crisis. Therefore, this study, adopting the Image Repair Theory as a framework, examined how the Oyo State Government of Nigeria repaired its reputation following the recent explosion that claimed many lives and left many injured. Data were sourced from responses and communication of the Oyo State Government on the official X page. Findings revealed that the government’s denial was not accepted by the public. However, the government managed its reputation through corrective action and compensation. This paper argues that government must not be discreet with its crisis response strategies. The analysis finds that a political leader’s presence and empathy are crucial in making compensation more effective as an image repair strategy.